SURFACE-ANALYSIS WITH A POSITION-SENSITIVE ATOM PROBE - Cerezo, A; Godfrey, T; Grovenor, C; Smith, G (1989)
A position-sensitive detector has been combined with time-of-flight mass spectrometry in a short-flight-path atom probe to yield an instrument in which both the chemical identity and surface position are obtained for individual atoms removed by field evaporation from the surface of a field-ion specimen. This enables thin films and surface layers to be analysed, not only with atomic-layer depth resolution, but also with sub-nanometre lateral resolution. The new instrument is described, and examples are presented showing the application of the technique to the study of the oxidation of metal surfaces, and surface segregation in an yttrium barium cuprate ceramic-oxide superconductor.